Enjoyment, Anxiety, and Reported Learning Effort of Saudi Military Cadets Studying English as a Foreign Language - Ali Falah Alqahtani (Kurdish Studies, 2024)
The impact of positive and negative emotions in the acquisition of a foreign language (FL) has increasingly come the interest of researchers in the field of second language acquisition (SLA). This study aims to investigate the influence of positive emotions (Foreign Language Enjoyment (FLE)), and negative emotions (Foreign Language Classroom Anxiety (FLCA)) on the perception of the Saudi English learners of their own proficiency in the FL, their knowledge of the FL vocabulary, and the effort they invest in the FL. The study was conducted in a military academy in Saudi Arabia and 148 male cadets studying English as the only foreign language voluntary participated in the study. Descriptive statistics showed that the participants a) obtained high scores in their English vocabulary test, b) were enjoying learning English at the academy, c) perceived themselves as competent English learners, d) were ready to invest more effort in their English learning. In addition, correlation analysis revealed a significant strong linear relationship between FLE and FL reported learning effort and a moderate linear relationship between FLE and FL perceived competence and their level of FL vocabulary knowledge, respectively. FLCA, on the other hand, negatively correlated with all the scales of the study. Finally, the regression analysis revealed that FL reported learning effort and FL perceived competence predicted a significant amount of the variance in FLE and FLCA. The regression analysis also revealed that FLE and FLCA combined with level of FL vocabulary knowledge contributed to the perception of this group Saudi cadets of their own competence in English.